Clinical risk factors for dengue shock syndrome in children - Jujun Junia; Herry Garna; Djatnika Setiabudi (Paediatrica Indonesiana, 2007)
Background Dengue shock syndrome (DSS) is a seriouscomplication of dengue hemorrhagic fever (DHF) which maycause death in more than 50% cases if not treated properly andpromptly. Clinical, viral, and epidemiological risk factorsdetermine the occurrence of DSS. Identifying risk factors for thedevelopment of shock in patients with DHF can increase theawareness of clinicians to perform a close monitoring.Objective To determine the clinical risk factors for DSS.Methods This case control study was conducted on DHF andDSS patients admitted to the Department of Child Health,Medical School, University of Padjadjaran, Dr. Hasan SadikinHospital Bandung from January 2004 to December 2005. Thesubjects were patients aged less than 14 years who fulfilled WHOcriteria (1997). The exclusion criteria were history of asthma,diabetes mellitus, sickle cell anemia, typhoid, sepsis, and measles.The risk factors for DSS were analyzed using chi-square test,calculation of odds ratio, and logistic regression analysis.Results Of 1,404 patients with suspected DHF, 600 met the studycriteria; 200 patients of DSS and 400 patients of DHF as controlgroup were identified. Univariate analysis showed that there wasassociation between DSS and age 5-9 years (OR=1.67, 95%CI1.08;2.58), overweight (OR=1.88, 95%CI 1.22;2.90), vomiting(OR=1.44, 95%CI 1.02;2.04), abdominal pain (OR=2.07,95%CI 1.46;2.92), and severe bleeding (OR=13.6, 95%CI5.96;31.03). By logistic regression analysis, it was found that age5-9 years (OR=1.62, 95%CI=1.03–2.53), overweight (OR=1.97,95%CI=1.29–3.08), and persistent abdominal pain (OR=2.08,95%CI =1.44–2.99) were independent risk factors for DSS.Conclusion Age 5-9 years, overweight, and persistent abdominalpain are the risk factors for DSS.